Quality Control of Edamame Products Using Statistical Quality Control (SQC) and Failure Mode Effect Analysis (FMEA) Methods in PT. XYZ - Fenny Novianti; Rr. Rochmoeljati (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2023)
PT. XYZ is a company engaged in the frozen food processing industry. One such product is Edamame. In the Edamame production process, defects such as pest defects, color defects, pod defects and mechanical defects that affect quality are still found. The purpose of this study was to determine the proportion of defects that most often occur and the factors that cause defects and to provide suggestions for improving the quality of edamame. The methods used are Statistical Quality Control (SQC) and Failure Mode Effect Analysis (FMEA). The SQC tools include check sheets, statistics, histograms, pareto charts, scatter diagrams, control charts, and fishbone diagrams. Then continue the FMEA analysis for suggestions for corrective action. Based on the results of research on Statistical Quality Control (SQC) it is known that the most dominant defects in edamame are pests (39.9%), then color (25.5%), pods (25.2%), and mechanics (9.4%) ). Based on the results of research on Failure Mode Effect Analysis (FMEA) it is known that the highest cause of problems with RPN 360 is lack of sanitation. Suggestions for improvement that can be proposed namely. Scheduling cleaning of the work environment area and sterilizing production machines and equipment.